Hubungan Sikap Kerja dengan Myofasial Trigger Poin Upper Trapezius Pada Pekerja Komputer Di Kecamatan Kartasura Kabupaten Sukoharjo - Rasyidi, Arba’Atur; Herawati, Isnaini (Universitas Pahlawan Tuanku Tambusai, 2024)
More than 1.5 billion students in higher education reported experiencing academic anxiety in April 2020. Personal control is essential to control academic stress, thereby fostering academic achievement. the direction of this research is to define the relationship between academic stress and academic self management in VIII semester undergraduate nursing students. the review study technique uses descriptive quantitative with a cross-sectional approach. The sample used was 79 samples obtained using the technique (total sample). The measurement tools used are Student-life stress inventory (SLSI) and Academic self-management. Data assessment using Rank spearman with a significant level (p-value) 0.05. Results: In the acquisition of research obtained there is no link between academic stress in students with academic self-management of 8th semester, undergraduate nursing students. from the acquisition of data assessment and calculation in this review study it can be concluded that the level of academic stress in final year students at Karsa Husada Health Science College Garut, the majority of informants in the low category, Academic Self-Management of students when preparing a thesis, the majority of informants at a moderate level, and Academic stress levels and academic self-management skills are unrelated in 8th semester undergraduate nursing students writing a thesis.